2012
DOI: 10.1128/jvi.00371-12
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the GM1 Binding Site of Simian Virus 40 VP1 Alter Receptor Usage and Cell Tropism

Abstract: h Polyomaviruses are nonenveloped viruses with capsids composed primarily of 72 pentamers of the viral VP1 protein, which forms the outer shell of the capsid and binds to cell surface oligosaccharide receptors. Highly conserved VP1 proteins from closely related polyomaviruses recognize different oligosaccharides. To determine whether amino acid changes restricted to the oligosaccharide binding site are sufficient to determine receptor specificity and how changes in receptor usage affect tropism, we studied the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 53 publications
(71 reference statements)
0
41
1
Order By: Relevance
“…This contrasts with our previous data showing that BKV-IV cannot efficiently transduce ganglioside-deficient Chinese hamster ovary (CHO) cells unless GT1b is added exogenously (33). To examine whether BKV-IV can transduce cell lines other than GM95 via a ganglioside-independent pathway, we performed a series of experiments in which ganglioside expression was knocked down on human A549 or ART cells using short interfering RNA targeting GM3 synthase (34). The results showed that GM3 synthase knockdown inhibited BKV-IV transduction (data posted at http://home .ccr.cancer.gov/Lco/BKV.asp).…”
Section: Fig 2 Bkv-neutralizing Titers Of Human Seracontrasting
confidence: 39%
“…This contrasts with our previous data showing that BKV-IV cannot efficiently transduce ganglioside-deficient Chinese hamster ovary (CHO) cells unless GT1b is added exogenously (33). To examine whether BKV-IV can transduce cell lines other than GM95 via a ganglioside-independent pathway, we performed a series of experiments in which ganglioside expression was knocked down on human A549 or ART cells using short interfering RNA targeting GM3 synthase (34). The results showed that GM3 synthase knockdown inhibited BKV-IV transduction (data posted at http://home .ccr.cancer.gov/Lco/BKV.asp).…”
Section: Fig 2 Bkv-neutralizing Titers Of Human Seracontrasting
confidence: 39%
“…To determine whether JCPyV is able to utilize gangliosides as functional receptors for infection, SVGA cells were supplemented with a panel of gangliosides prior to infection with JCPyV Mad-1, Mad-1/WT3C, BKPyV, and SV40. BKPyV utilizes the gangliosides GD1b and GT1b as functional receptors, while SV40 utilizes GM1, and exogenous ganglioside addition has been previously demonstrated to enhance infection (25,59). Interestingly, supplementation of cells with gangliosides GM1, GM2, GD1a, GD1b, and GT1b did not alter JCPyV infection compared to that for the dimethyl sulfoxide (DMSO)-treated control.…”
Section: Exogenous Addition Of Gangliosides Does Not Enhance Jcpyv Inmentioning
confidence: 89%
“…7B), indicating that both strains of JCPyV require 5-HT 2 Rs for productive infection. In contrast, BKPyV and SV40 can still switch their glycan receptor specificity through a single VP1 point mutation, but these viruses both utilize lipid-linked ganglioside receptors and share a cholesterol-dependent entry mechanism (25,59). Binding of JCPyV to LSTc may induce organizational and/or structural changes at the plasma membrane that favor interactions with the entry receptor 5-HT 2 R.…”
Section: Discussionmentioning
confidence: 99%
“…SV40, which is closely related to BKV and JCV, is known to require the sialylated ganglioside GM1 for infectious entry into many (but not all) cell types (Magaldi et al, 2012). Prior work has not addressed the possibility that GAGs might be involved in SV40 infectious entry.…”
Section: Resultsmentioning
confidence: 99%